Effects of exercise with or without β-hydroxy-β-methylbutyrate supplementation on muscle mass, muscle strength, and physical performance in patients with sarcopenia: a systematic review and meta-analysis - Feng, Yiwei; Chen, Peng; Li, Tao; Wan, Ping; Shi, Rengfei (Frontiers in Nutrition, 2024)
Objectives: This systematic review and meta-analysis aimed to assess the effects of exercise with/without β-hydroxy-β-methylbutyrate (HMB) supplementation on muscle mass, muscle strength, physical performance, and body composition in patients with sarcopenia.A literature search for randomized controlled trials (RCTs) on the effects of exercise with or without HMB supplementation on muscle mass, muscle strength, physical performance, and body composition in patients with sarcopenia was conducted using PubMed, Web of Science, EBSCO, The Cochrane Library, EMBASE, Scopus, Science Direct, China Knowledge Resource Integrated Database (CNKI), and Wan Fang database. The search was limited to studies published up to April 2024 for each database. The outcome measures included muscle mass, muscle strength, physical performance, and body composition. The Cochrane Risk of Bias Assessment Tool was used to evaluate the quality of the included literature, and RevMan 5.4 software was employed to perform a meta-analysis of the outcome indicators.Results: Five RCTs involving 257 elderly patients with sarcopenia were included in this study. Metaanalysis showed that in terms of physical performance, exercise with HMB supplementation significantly increased gait speed in sarcopenic patients compared to the exercise combined with the placebo group (SMD=0.48, 95% CI: 0.15 to 0.82, p=0.005), but exercise combined with HMB supplementation did not have significant effects on SMI (SMD=0.06, 95% CI: -0.20 to 0.32, p=0.66), grip strength (SMD=0.23, 95% CI: -0.05 to 0.52, p=0.11), five-time chair stand test (SMD=-0.83, 95% CI: -1.88 to 0.21, p= 0.12), fat-free mass (SMD=0.04, 95% CI:-0.26 to 0.35, p=0.78), BMI (SMD=-0.09, 95% CI:-0.43 to 0.25, p=0.60), and fat mass (SMD=0.01, 95% CI:-0.25 to 0.27, p=0.94).The current evidence indicates that exercise with HMB supplementation may enhance physical performance in patients with sarcopenia compared to exercise with the placebo group. However, the effects on muscle mass, muscle strength, and body composition are likely minimal. The above findings are limited by the number of included studies and require further validation through high-quality studies.